Life in sympatry: coexistence of native Eurytemora affinis and invasive Eurytemora carolleeae in the Gulf of Finland (Baltic Sea) - Natalia Sukhikh; Anissa Souissi; Sami Souissi; Anne-Catherine Holl; Nikolaos V. Schizas; Victor Alekseev (Oceanologia)
Summary: The invasion of exotic species into native ecosystems is becoming a crucial issue in global biology. Over the last ten years, at least 45 invasions of aquatic species have been reported in the eastern part of the Gulf of Finland; the majority of them were introduced through ballast water. Recently, invasion of the estuarine calanoid copepod Eurytemora carolleeae (Temoridae), originating from North America, has been reported in several European estuaries and particularly in the Gulf of Finland. This species is morphologically very similar to the native Eurytemora affinis, but it is easily discriminated by molecular markers. In this study, we monitored the distribution area of the invasive copepod species in European waters, as well as the population structure of (native) E. affinis and (invasive) E. carolleeae, from 2006 to 2018 in the Gulf of Finland. The population density of E. affinis was significantly higher, compared to E. carolleeae, during most of the study period. The only exception was Neva Bay in 2010, wherein the invasive species dominated possibly due to high temperatures and differences in the levels of fish predation. The reproductive performance of E. carolleeae was also higher than that of E. affinis. These results show different population dynamics between the two species. It was revealed that invasive E. carolleeae develops in some of the very same habitats as native E. affinis, thereby potentially becoming a significant component of the zooplankton in the studied area. Moreover, invader has the potential to displace native E. affinis. Keywords: Eurytemora species, Copepoda, Zooplankton, Invasive and native species, Gulf of Finland